THE RELATIONSHIP BETWEEN BREASTFEEDING TECHNIQUE AND THE INCIDENCE OF NIPPLE BLISTERS IN POST PARTUM WOMEN AT PMB HJ. YETTI LATIF S.ST - ARDIANTI, ALIMAH; YUNTARISA, ATIKA PRADANA; PRASETYANINGSIH, PRASETYANINGSIH (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
One of the problems that often occurs in breastfeeding mothers is the lack of knowledge about breastfeeding. Problems that are often experienced by mothers such as nipple blisters, breast milk dams, breast pain, causing mothers not to breastfeed their babies. Another problem is that many husbands still have the wrong opinion, consider it trivial and just be a passive observer of the breastfeeding behavior of mothers and babies. This study aims to determine the relationship between breastfeeding techniques and the incidence of nipple blisters in postpartum women at PMB Hj. Yetti Latif S.ST in 2024. This research method uses quantitative research which is analytic in nature with a cross-sectional approach. This research was conducted in 1-29 August 2024. The population of this study were 82 postpartum mothers. The number of samples taken as many as 45 postpartum women with accidental sampling technique. Univariate and Bivariate data processing using chi-square analysis. Statistical results of the chi-square test p value 0.000. Thus, there is a relationship between breastfeeding techniques and the incidence of nipple blisters in postpartum women at PMB Hj. Yetti Latif S.ST in 2024. It is expected that breastfeeding mothers should increase their knowledge and information about proper breastfeeding techniques through various sources of information in order to reduce the number of nipple blisters. It is hoped that it can be used as a basis for further research, namely the relationship between maternal knowledge of breastfeeding techniques and the state of nipple blisters with other more specific variables, so that for further research this can be further refined